1991
DOI: 10.1007/bf01297028
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of oral cisapride in symptomatic upper gut dysmotility

Abstract: We conducted a 12-month trial of cisapride (10 mg three times a day) in 21 patients with gastric stasis due to clinically and manometrically diagnosed gastroparesis (N = 9; seven due to diabetes) or chronic intestinal pseudo-obstruction (N = 12). Radionuclide solid-liquid gastric emptying tests were performed at baseline and at the end of the 12-month period. Symptoms were assessed monthly by diary and every three months by the investigators; frequency and severity of symptoms were scored in a standardized man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(59 citation statements)
references
References 14 publications
3
56
0
Order By: Relevance
“…Cisapride is thought to promote gastric emptying mainly by acting as a partial agonist at 5-hydroxytryptamine 4 receptors in the myenteric plexus and thereby facilitating cholinergic excitatory neurotransmission [142,143]. In uncontrolled singledose investigations in diabetic patients, the agent was found to accelerate emptying [145,153], but the results of studies extending over longer periods of time have been ambiguous [154,155].…”
Section: Treatments Aimed At Accelerating Gastric Emptyingmentioning
confidence: 99%
“…Cisapride is thought to promote gastric emptying mainly by acting as a partial agonist at 5-hydroxytryptamine 4 receptors in the myenteric plexus and thereby facilitating cholinergic excitatory neurotransmission [142,143]. In uncontrolled singledose investigations in diabetic patients, the agent was found to accelerate emptying [145,153], but the results of studies extending over longer periods of time have been ambiguous [154,155].…”
Section: Treatments Aimed At Accelerating Gastric Emptyingmentioning
confidence: 99%
“…Rikkunshito is composed of over 100 compounds, including 8 major constituents, and a prokinetic action via NG-nitro-L-arginine could be considered as another candidate mechanism for the symptom relief [39,40]. Prokinetic drugs, including erythromycin, cisapride, metoclopramide, and domperidone, may accelerate gastric emptying after gastrectomy and alleviate post-gastrectomy symptoms [40][41][42][43]. In adult patients with diabetic gastroparesis, normalization of electrical activity has been seen after domperidone administration [44].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials cisapride demonstrated benefit (not always consistent) in both the short-and long-term therapy of gastroparesis and dyspepsia. 18,19 However, all of this promise came to naught when reports of serious cardiac arrhythmias, related to QT interval prolongation 20,21 began to appear. The withdrawal of cisapride spurred interest in the development of alternative 5-HT 4 agonists.…”
Section: Serotonergic Agonistsmentioning
confidence: 99%